Karakteristik Pasien Ikterus Obstruktif Et Causa Batu Saluran Empedu - Yusmaidi Yusmaidi; Rakhmi Rafie; Annisa Permatasari (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Obstructive jaundice is jaundice caused by bile obstruction. Common bile duct stone are one of the most common causes of obstructive jaundice. The purpose of this study to determine the characteristics of the patients with obstructive jaundice et causa common bile duct stone in RSUD Dr. H. Abdul Moeloek Bandar Lampung in 2017-2018. This study was retrospective descriptive which used secondary data from medical records. Purposive Sampling technique was used to collect the data. The sample of this study were 35 patients . The most common cases attacked 18 patients aged 46-65 years old (51,4%) and 22 female patients (62.9%). The main complaints and physical examinations were mostly on the sclera and jaundice skin as much as 100%. Based on the results of laboratory examination and ultrasound, it showed that 51.4% normal leukocytes, 85.7%. intrahepatic bile duct widening and 57.1% operative measures are performed. he characteristics were mostly in women aged 51-60 years old with the main complaints and physical examination were sclera and jaundice skin, normal leukocytes, intrahepatic bile duct widening, and operative measures are performed